The agricultural groundwater revolution : opportunities and threats to development - Giordano, Mark; Villholth, Karen G. (Comprehensive assessment of water management in agriculture series, 2007)
This book addresses the issues of using groundwater in agricultural production in the developing world. By addressing the problems associated with the degradation and overexploitation of the groundwater resources, it explores the practiced and potential methods that meet the massive challenges of agricultural water management in the context of agricultural development. The book is divided into three parts plus two final chapters. Part I provides regional overviews of agricultural groundwater systems covering much of the developing world. The regions include 'traditional' use areas such as South Asia, China and the Middle East/North Africa where groundwater already contributes substantially to existing agricultural economies. It also includes two areas, sub-Saharan Africa and Central America. Part II presents an overview of three major governance paradigms that have been, or might be, employed to address challenges facing groundwater management. Part III provides a series of case studies that examine how these governance paradigms have actually functioned on the ground. A chapter concludes the book with n overview of the state of affairs in agricultural water use in the developing world, the opportunities and threats for the resource to continue contributing t global food supply and to lifting farmers out of poverty and into the future, agricultural or not, tat they most desire.